Ślady miejsc wspólnych. O zaletach pojęcia toposu dla badań nad Zagładą - Wolski, Paweł (Narracje o Zagładzie [czasopismo zamknięte], 2016)
Traces of the Common Places. On the Advantages of the Notion of a Topos for the Holocaust Studies The author proves the relevance of the notion of a topos for the studies on the narratives of the Shoah, emphasising its unique status of the phenomenon which on the one hand is a ready‑made interpretation of a given situation/event/image, and on the other shows the contextual oscillations of their meanings, actualised in a specific use. Having noted the most interesting contemporary ways of using topoi in the humanities (Reinhardt Koselleck, et al., Geschistlische Grundbegriffe, Mieke Bal, Travelling Concepts in the Humanities etc.) and their less known exegeses in literary theory (e.g. Paolo Valesio, Novantiqua), then having referred to the proto‑classification of the common places in the Holocaust discourse (Słowa niewinne, LTI, Encyklopedia getta etc.), and finally having commented upon the contemporarily used tools of the related studies (imagery, trace etc.), the author outlines the project of the dictionary of the topoi of the Shoah in Polish literature, film, journalism and other narrative forms. Key words: theory, topos, structure, imagery, trace